TOLERANCE OF MILK FORMULAS FOR INFANTS AND THE PROBLEM OF QUALITATIVE PROTEIN COMPOSITION - A. Shaafsma; A. A. Davydovskaya; T. I. Garankina; S. G. Gribakin (Вопросы современной педиатрии)
The process of milk formulas for infants production is complex and multistage and includes the thermal processing. There is data, that different regimens of thermal processing influence on the structure of the protein-carbohydrate complexes, which can affect the formula’s protein uptake. It was shown, that interaction between complex protein units of the formula and the cells of the Peyer’s patches increased the risk of allergic reactions development in infants with predisposition to atopy. The influence of denaturation of milk formulas on the tolerance of them is discussed in this article.